Development of a geological model useful for the study of the natural hazards in urban environments: an example from the eastern sector of Rome (Italy)(°) - Luberti, Gian Marco; Prestininzi, Alberto; Esposito, Carlo (Italian journal of engineering geology and environment, 2015)
Detailed knowledge of the subsoil setting is an extremely important issue for a correct risk reduction policy, especially when dealing with urban areas hosting cultural heritage, which enhance risk conditions even at low geo-hazard levels, as in the case of Rome. In general, the reliability of risk assessments related to geo-hazards is strictly dependent on the resolution of the reference geological model. The study presented here exemplifies an integrated methodology aimed at refining the knowledge of the geological setting in unique urban